Maxillary second molar with five root canals: a case report - Ljiljana Kulić; Jelena Krunić; Nikola Stojanović; Dajana Nogo-Živanović (Биомедицинска истраживања, 2014)
Introduction: . The main goal of each root canal treatment therapy is the thorough cleaning and obturation of the entire root canal system. The main reasons for endodontic failure are incomplete instrumentation, inadequate cleaning, insufficient canal obturation, and the presence of untreated canals. Therefore, a comprehensive understanding of the root canal morphology is essential and will help to reduce endo - dontic failure caused by incomplete root canal preparation and obturation. The purpose of the present clinical report is to describe the second maxillary molars with two separated palatal roots and five root canals, and the endodontic treatment procedures for this tooth. Case Outline . A case of a four-rooted maxillary second molar in a 27-year-old male patient is reported. After clinical and radiographic examination, two separate palatal roots were detected. The tooth was treated by endodontic retreatment in two visits. After 15-day intracanal medication, the root canals were filled with guttapercha cones and sealer. Conclusion: . The case report underlines the importance of complete knowledge about root canal mor phology and that abnormalities must always be considered when performing endodontic treatment.
Keywords: anatomical variations; maxillary second molar; endodontic treatment